Relationship of Inflation, BI Rate and Deposit Interest Rate - Danang Indrajaya (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to model the relationship between the inflation rate, BI rate, and deposit interest rates, then analyze the model, and provide forecasting and structural analysis of the model. Therefore, the method used in this study is Vector Error Correction Model analysis which is applied to time series data of the inflation rate (CPI), BI rate, and deposit interest rates. The results of the model analysis show that the policy of changing the BI rate has an effect on the rise and fall of the inflation rate (CPI) and fluctuations in the deposit rate (deprate). The BI rate is also influenced by two other variables (CPI and Deprate), but the biggest influence is from the variable BI Rate itself, and CPI and Deprate are mutually influencing (causality effect), but like the BI rate, the most influential variable is the lag variable of each of these variables